Toxicity of Soursop (Annona Muricata L) Leaf Extract and Patchouli (Pogostemon Cablin Benth) Leaf Extract to American Cockroach (Periplaneta Americana) - Ryhan Sasdar; Syamsiah Syamsiah; Andi Mu'nisa (Fakultas MIPA UNM, 2023)
This study aims to determine the toxicity of soursop leaf extract (Annona muricata L.) and patchouli leaf extract (Pogostemon cablin Benth.) on the mortality of the American cockroach (Periplaneta americana). The extract was prepared using the maceration method, using distilled water as a solvent. Soursop and patchouli leaf extracts with a concentration of 5% were sprayed as much as 2 ml on each American cockroach. The results of the study were cockroach mortality data for 1-120 hours with observations every 1, 3, 6, 12 and 24 hours. As for the results obtained, the administration of soursop leaf extract cockroach mortality at the 24th hour was 66.67% and at the 48th hour 100% cockroach mortality. Whereas in the administration of patchouli leaf extract cockroach mortality at the 96th hour was 66.67% and at the 120th hour 100% cockroach mortality.